2012
DOI: 10.1089/mdr.2011.0064
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Streptomycin Epidemiological Cut-Off Values forSalmonellaandEscherichia coli

Abstract: This study was conducted to elucidate the accuracy of the current streptomycin epidemiological cut-off value (ECOFF) for Escherichia coli and Salmonella spp. A total of 236 Salmonella enterica and 208 E. coli isolates exhibiting MICs between 4 and 32 mg/L were selected from 12 countries. Isolates were investigated by polymerase chain reaction for aadA, strA, and strB streptomycin resistance genes. Out of 236 Salmonella isolates, 32 (13.5%) yielded amplicons for aadA (n = 23), strA (n = 9), and strB (n = 11). N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…In the 18 K. pneumoniae strains that had MICs≥6 µg/ml, streptomycin resistance genes could only be found in the 6 strains that had MICs≥12 µg/ml. This result was similar to the previous study in which the streptomycin epidemiological cut-off values were recommended as WT≤16 µg/ml for Salmonella and WT≤8 µg/ml for E. coli [2] . The aadA gene was found in the four Klebsiella strains exhibiting streptomycin MIC 12 or 16 µg/ml.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the 18 K. pneumoniae strains that had MICs≥6 µg/ml, streptomycin resistance genes could only be found in the 6 strains that had MICs≥12 µg/ml. This result was similar to the previous study in which the streptomycin epidemiological cut-off values were recommended as WT≤16 µg/ml for Salmonella and WT≤8 µg/ml for E. coli [2] . The aadA gene was found in the four Klebsiella strains exhibiting streptomycin MIC 12 or 16 µg/ml.…”
Section: Discussionsupporting
confidence: 91%
“…The aadA gene was found in the four Klebsiella strains exhibiting streptomycin MIC 12 or 16 µg/ml. The low-level resistance to streptomycin conferred by aadA can also be found in Salmonella and E. coli [2] , [7] , [44] . No streptomycin resistance was found to be caused by rpsL mutations in any of the 127 clinical strains of K. pneumoniae .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NARMS program has long used Ն64 mg/liter to define resistance and detected it with a narrow dilution range (32 mg/liter to 64 mg/liter) around the breakpoint. Further testing using a broader dilution range (2 mg/liter to 64 mg/liter) revealed that Ն32 mg/liter better reflects the presence of resistance genes in Salmonella and E. coli (30), as has been found by others (31). Based on these data, the NARMS will change interpretive criteria for streptomycin resistance in Salmonella in future reports.…”
Section: Discussionmentioning
confidence: 52%